Ultrasonic cleaning of polytetrafluoroethylene (PTFE) membrane fouled by natural organic matter (NOM) - Genuino, Divine Angela D. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Natural organic matter (NOM) causes severe fouling during membrane filtration. Chemical cleaning is considered to be the most effective way in eliminating NOM fouling, but its application is highly discouraged due to severe damage on membrane materials and generation of secondary pollution, i.e. chemical wastes. The use of ultrasound as an alternative cleaning technique of NOM-fouled membranes is not yet widely explored. In this research, the effect of ultrasonic cleaning of PTFE membrane fouled by pre-coagulated humic acid-bentonite solution was investigated. Chemical coagulation prior to microfiltration improved turbidity and TSS removal by 9.54% and 11.43%, respectively. Experimental data fitted to constant pressure filtration models determined the sequence of dominant fouling mechanism as follows: (i) membrane resistance-limited, (ii) pore blocking resistance-limited, and finally, (iii) cake formation resistance limited. Relative membrane permeability of 53.02 and flux recovery of 45% were achieved when continuous ultrasonic cleaning was done at a probe distance of 2.0 cm, total cleaning time of 25 min, coagulant dose of 15 mg/L, and ultrasonic power of 15 W. Ultrasonic cleaning was found to be more effective than hydraulic cleaning in terms of flux recovery. Compared to chemical cleaning, it was found to be a competitive and safer alternative in mitigating membrane fouling caused by natural organic matters.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Polytef